Export Potential of the Russian Pharmaceutical Market and its Prospects - Pyatigorskaya, Natalia; Meshkovski, Andrei; Aladysheva, Zhanna; Beregovykh, Valery; Belyaev, Vasily; Ivashechkova, Natalia; Shabalina, Marina (International Journal of Engineering and Technology, 2018)
Export of medicines is one of the most profitable businesses, which attracts the attention of an increasing number of producers. The international medicines’ trade largely depends on national or regional regulatory mechanisms. In addition, the export terms and conditions differ for various categories of medicines. Innovative drugs account for the main share of the global medicines’ export. Therefore, export of innovative drugs developed in Russia to advanced countries is the most economically profitable direction. Export of generic drugs can bring considerable revenue to the producer and the state, but import substitution by releasing generic drugs weakens the innovative direction of studies and production. The import substitution policy targets manufacturers of medicines to produce generic drugs, as well as products intended, mainly or exclusively, for sale within the country. One of the ways to improve the efficiency of the entire pharmaceutical sector is international cooperation.